Effect of cutting parameters on machining induced distortion in thin wall thin floor parts / Garimella Sridhar and Poosa Ramesh Babu - Sridhar, Garimella; Babu, Poosa Ramesh
This paper presents experimental study on the effect of machining parameters viz., feed, speed, width of cut and depth of cut on machining induced distortion. Machining experiments were done using Response Surface Methodology. Optimization of machining parameters for minimum machining induced distortion was also carried. Four factor, three level Box-Behnken method with analysis of variance is used in dry machining aluminium alloy 2014 T651 with two flute solid carbide Ø 10 mm milling tool. Machining simulation experiments were also carried out using Deform 3D software to know the effects of these parameters on forces and temperature generated for correlation with machining induced distortion. Results show that feed, width of cut and depth of cut have significant effect on machining induced distortion. It is observed that, there is an increase in machining induced distortion due to increase in cutting forces in Z – direction and temperature with increase in feed, depth of cut and width of cut during milling thin-wall thin-floor components. The optimal combination of cutting parameters arrived with target values of distortion and twist less than 0.09 mm is feed 0.18 to 0.2 mm/tooth, speed 180 to 210 m/min., width of cut 5.6 mm and depth of cut 0.4 mm.